Peran Kontrol Diri Dimediasi Motivasi Belajar pada Perilaku Cyberloafing Mahasiswa - Agnes Priccilia Pakpahan; Salamiah Sari Dewi; Amanah Surbakti (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
The rapid advancement of technology does not always produce positive outcomes for university students. One emerging negative behavior is cyberloafing, defined as the use of internet access for non-academic purposes during learning activities. Self-control and learning motivation are considered important psychological factors that may help reduce cyberloafing behavior among students. This study aimed to examine the mediating role of learning motivation in the relationship between self-control and cyberloafing behavior among students of the Faculty of Economics at Universitas Medan Area. A quantitative research approach was employed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The sample consisted of 254 students selected through purposive sampling with the assistance of the Slovin formula. Data were collected using three instruments: a self-control scale, a cyberloafing behavior scale, and a learning motivation scale. The results indicated that self-control had a significant negative effect on cyberloafing behavior (Î² = âˆ’0.248, p < 0.05), learning motivation also had a significant negative effect on cyberloafing behavior (Î² = âˆ’0.252, p < 0.05), and self-control had a significant positive effect on learning motivation (Î² = 0.754, p < 0.05). Furthermore, learning motivation was found to significantly mediate the effect of self-control on cyberloafing behavior (Î² = âˆ’0.190, p < 0.05). These findings demonstrate that higher levels of self-control and learning motivation are associated with lower levels of cyberloafing among university students. This study highlights the importance of strengthening students’ self-control and learning motivation as effective strategies to reduce cyberloafing behavior in academic settings.